Saphenous Vein Graft Perforation During Percutaneous Coronary Intervention - A Nightmare to be Avoided - Surender Deora; Sanjay C Shah; Tejas M Patel (Heart Views, 2015)
Percutaneous coronary interventions (PCIs) of saphenous vein grafts (SVGs) is challenging and is associated with adverse short- and long-term clinical outcome as compared to native coronary arteries. SVG perforation is rare but catastrophic and needs immediate attention. Various factors predisposing for SVG perforation are old degenerated graft, ulcerated plaque, severe fibrotic, or calcified lesion necessitating high pressure balloon or stent inflation, use of intravascular ultrasound (IVUS) or other atheroablative devices. Management includes prolonged balloon occlusion, reversal of anticoagulation, use of covered stent, and emergency pericadiocentesis if required.